87.9k views
4 votes
Substitution Method 3x - y = 22 y = 2

1 Answer

1 vote

Given


2x-y=22

For y=2

First replace the value of y in the formula


\begin{gathered} 2x-y=22 \\ 2x-2=22 \end{gathered}

Next pass "-2" to the other side of the equation, to do so, add it to both sides of the equation


\begin{gathered} 2x-2+2=22+2 \\ 2x=24 \end{gathered}

Finally, since x is being multiplied by 2, divide both sides by 2 to determine the value of x


\begin{gathered} (2x)/(2)=(24)/(2) \\ x=12 \end{gathered}

User Zrb
by
5.4k points